Power of Religious Beliefs and Coping with Cancer: Opinions of Iranian Parents - Mazhari, Fariba (Journal of religion and health, 2021)
Childhood cancer as a stressful event has many consequences for both the parents and their children. The aim of the study was to assess the coping strategies used by Iranian parents of children with cancer. The present study was conducted through convenience sampling with the participation of 205 parents with at least one child with cancer referred to the oncology ward, in the southeast of Iran. The Coping Health Inventory for Parents was used to measure parental coping strategies. Results showed that the highest and the lowest mean coping score belonged to the dimensions of social support and medical factors, respectively. Briefly, “Belief in God” and “Gratefulness for his Blessings” were the most helpful coping strategies among parents. Based on results of this study, it seems necessary for nurses to be aware of all aspects of human existence, including religion and spirituality as strong sources of power for parents to adapt with the illness of their child. Also, providing interventions to teach effective coping skills to parents may reduce their distress and improve their quality of life.